Swedish multiculturalism: Newly arrived Arab immigrants in Malmö - Mihaela Vancea (Sortuz)
Vancea develops a deep case study of the initial settlement of newly arrived immigrants in one Swedish village. Based on the information gathered on a scholar program designed for immigrants, she analyses the clash between immigrant's hopes and the mainstream components of Swedish immigration policy. Successfully, she combines qualitative methods with reflections on political philosophy to conclude that Swedish immigration policy seeks cultural integration despite its rhetoric on multiculturalism and respect for other's identity.